MEMBANGUN BUDAYA LITERASI MEMBACA DENGAN METODE READ ALOUD (MEMBACA NYARING) PADA SISWA SEKOLAH DASAR NEGERI SELAPAJANG II, KECAMATAN CISOKA, KABUPATEN TANGERANG - Yeni Khoirunnisa Agustiani; Fat'Chatus Chanifa Jikhan; Muhammad Lukman Hakim; Dwisapto Yusuf Pradana (SEBA: Jurnal Pengabdian kepada Masyarakat, 2025)
Reading literacy is an important foundation for building Indonesia's future generation, capable of critical thinking and global competitiveness. Reading can encourage someone to have extensive knowledge and be able to understand all information well. One method to build a culture of reading literacy is read aloud method. This community service activity was carried out at one of the elementary schools in Tangerang Regency, namely Selapajang II Elementary School, Cisoka District, Tangerang Regency. This community service activity was carried out by introducing and teaching children the reading aloud method using story books for grade 6 students. The method of implementation of this activity was carried out by providing socialization to students about the reading aloud method, reading aloud practice, and game sessions and giving prizes to students. The results of this activity showed positive achievements as seen from the enthusiasm and enthusiasm of the students. This activity is expected to increase students' interest in reading through the reading aloud method. Keywords: Reading Literacy, Read Aload, Elementary School.